Treating alcohol-related liver disease from a public health perspective - Hydes, T.; Gilmore, William; Sheron, N.; Gilmore, I. (Elsevier BV, 2019)
Herein, we describe the evolving landscape of alcohol-related liver disease (ALD) including the current global burden of disease and cost to working-aged people in terms of death and disability, in addition to the larger spectrum of alcohol-related heath complications and its wider impact on society. We further review the most effective and cost-effective public health policies at both a population and individual level. Currently, abstinence is the only effective treatment for ALD, and yet because the majority of ALD remains undetected in the community abstinence is initiated too late to prevent premature death in the majority of cases. We therefore hope that this review will help inform clinicians of the “public health treatment options” for ALD to encourage engagement with policy makers and promote community-based hepatology as a speciality, expanding our patient cohort to allow early detection, and thereby a reduction in the enormous morbidity and mortality associated with this disease.